A Review of Early Motor Issues in Young Children With Autism Spectrum Disorder. Issue 4 (October 2022) - Hebert, Elizabeth Baltus; Nolan, Karen W.; Smith, Katie Nicole
Abstract : The cardinal features of autism spectrum disorder (ASD) are recognized to include impairments in communication, social interactions, and restricted, repetitive behaviors and stereotyped interests. However, many children with ASD also have motor activity limitations that are often overlooked. The purpose of this review is to summarize the literature on neuromotor impairment and motor activity limitation in children with ASD. A literature search was conducted of citations from 1998 through 2021 using PubMed, EMBASE, and PsycINFO. Twenty-three search terms were used to encompass diverse articles focused on children with autism and motor activity. The search resulted in 78 articles that included the search terms and were also consistent with the aims of this literature review. The potential significance of motor activity limitations on development from an early age is explored and recommendations are offered for more holistic surveillance in children with ASD, which can facilitate early access to services when indicated.